STUDI EKONOMI RENOVASI PROPULSI KAPAL PATROLI â€œPARIKESITâ€ - Ridwan, Mohd (Gema Teknologi, 2011)
Mohd Ridwan, in this paper explain that new replacement main engine and propeller ship needs to be done with technical economic considerations. Main engine maintenance costs that have entered the age of 15 years improved each annualy, and fuel consumption increases. So that needs to be done renovations main engine by selecting the main engine in accordance with the propeller or propeller can also perform renovations. For this purpose needs the engineering and economic studies to decrease over 10% of the ship operational costs. Keywords : Main engine, Propeller, Operational costs